Cross-cultural management in China: Competencies of Chinese business students - Cramer, Tobias (Journal of Eastern European and Central Asian Research (JEECAR), 2018)
The ability to deal with cross-cultural differences has grown in importance due to the increasing number of Sino-foreign cooperation and the fact that more and more Chinese companies are investing abroad. The present study examines cultural awareness and cognitive cultural intelligence (cognitive CQ) of Chinese undergraduate students. The results show that Chinese undergraduate business students are moderately well culturally aware and they display average cognitive CQ.